The Role of Islamic Inheritance Law with a Maqasid al-Shariah Approach in Addressing the Challenges of Social Justice for Women - Syifa Mutiara Putri Heriandita; Farah Farouk Alwyni; Mohammad Izdiyan Muttaqin; Mulawarman Hannase (AJIS: Academic Journal of Islamic Studies, 2025)
Social justice is a fundamental principle in Islam, encompassing the regulation of inheritance law to ensure fair wealth distribution, particularly for women. Although inheritance rules in the Quran and Hadith grant rights to women, challenges such as patriarchal dominance, lack of legal awareness, and evolving roles of women in families often hinder the implementation of justice. Using the maqasid al-shariah framework as a theoretical approach, this study aims to analyze Islamic inheritance law's role in ensuring women's social justice. The methodology employed is a qualitative approach based on library research. It examines various Islamic legal sources, such as the Quran and Hadith, to understand women's inheritance rights and their obstacles in practice. Furthermore, this study explores solutions through ijtihad, hibah (gifting), and wasiyyah (bequests) to address these challenges. The findings indicate five key challenges women face in achieving social justice in inheritance law and four practical solutions to overcome these issues. This study seeks to contribute original insights into Islamic inheritance law's role in addressing women's social justice issues through the maqasid al-shariah approach.